Analisis Pengaruh Perubahan Kontrak (Addendum) Akibat Force Majeure Menggunakan SPSS dan SmartPLS : (Studi Kasus: Proyek BKS-LPD Kabupaten Karangasem) - I Komang Agus Ariana; Ravika Nur Melinda; Dewa Ayu Putu Adhiya Garini Putri; Putu Ariawan (Jurnal Teknik Sipil, 2023)
Due to delays brought on by force majeure, the BKS-LPD Building Construction Project required a contract change order (addendum) to give the service providers a chance to finish the work. According to earlier studies, contract change orders (addendum) have an impact on the price and timeline of the work. The aim of the research is to use the SPSS and SmartPLS tools to find out the result of the impact of the contract change ordered due to force majeure. The research method utilized consists of retesting the questionnaire's results from earlier research utilizing the SPSS and SmartPLS computer tools. The purpose of the retesting is to identify any differences between the analysis results from the SmartPLS program and the analysis results from earlier research conducted using SPSS, as well as to evaluate the precision of each statistical software. According to the results of the SPSS, the addendum significantly affects costs by 12.6%. Only by 4.9% and 0.4% did the addendum's impact on quality and time become insignificant. The analysis's results for the SmartPLS program revealed that the addendum significantly impacted cost and quality by 11.9% and 12.6%, respectively. The addendum's impact is insignificant because it is just 0.4% on time. Differences in margins or limitations on validity test requirements that are quite dissimilar in the need to qualify for each of these statistical programs lead to differences in analysis results between the SPSS and SmartPLS programs, especially in the relation of addendums to quality. Due to this, while using the SmartPLS tool for analysis, several variable indicators were left out.